CHARACTER DEVELOPMENT OF NATHANIEL FROM JONATHAN STROUD’S BARTIMAEUS TRILOGY: THE AMULET OF SAMARKAND - Delia Arnindita Larasati (Universitas Gadjah Mada, 2012)
This research is aimed at studying about the character development of someone. The development character is based on a novel Bartimaeus Trilogy: The Amulet of Samarkand by Jonathan Stroud. The discussion of this research is limited to the analysis of Nathaniel’s character development as the main character.The study of character development of Nathaniel from ordinary little boy to ambitious boy is important in this story because he is the main character and to prove that someone’s personality changed because of his past. For this reason, an objective approach suggested by Abrams is applied in this research. The definition of character development by Griffith which is used as the reference is also used to know whether the dynamic characteristic of Nathaniel is in accordance with the theories suggested by Griffith. The Library research is used in collecting the data. It includes doing intensive reading on the novel and finding the evidences through the plot.By doing the analysis, it turns out that Nathaniel’s character has changed from ordinary to ambitious boy because of his past. This finding is actually in accordance with Griffith’s theory of dynamic characteristic.